2012
DOI: 10.1111/j.1365-2494.2011.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Potency of microbial inocula from bovine faeces and rumen fluid for in vitro digestion of different tropical forage substrates

Abstract: In vitro ruminal fermentation techniques rely on the availability of fistulated ruminants for rumen fluid (RF), a major constraint for resource-poor institutions. An alternative would be to use faecal microbes. This study was therefore designed to compare the potency of fresh bovine faeces against RF as sources of microbial inocula for fermenting six contrasting tropical forages using the Tilley and Terry (Journal of British Grassland Society, 18, 104-111) technique. Faecal inocula were prepared at concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…For example, Akhter et al [8] obtained significant regression equations between in vitro OMD of eight forages determined with sheep rumen liquor and cow faeces. Another study [6] showed that the OMD of different forages estimated with faecal inoculum was comparable to the OMD determined with cow rumen fluid after 48 h of incubation. Regarding GP, a study [7] showed that in vitro total GP was greater for feeds incubated with cow rumen inoculum as compared to cow faecal inoculum.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…For example, Akhter et al [8] obtained significant regression equations between in vitro OMD of eight forages determined with sheep rumen liquor and cow faeces. Another study [6] showed that the OMD of different forages estimated with faecal inoculum was comparable to the OMD determined with cow rumen fluid after 48 h of incubation. Regarding GP, a study [7] showed that in vitro total GP was greater for feeds incubated with cow rumen inoculum as compared to cow faecal inoculum.…”
Section: Introductionmentioning
confidence: 80%
“…The rumen fluid was collected before the morning meal and was immediately strained through four layers of cheesecloth into a pre-warmed (39 °C) flask with CO 2 and mixed with the buffer solution [10] in a 1:2 ratio. Faecal samples were first mixed with the same buffer solution (at the same 1:2 ratio) and maintained for thirty minutes at 39 °C with CO 2 , and then strained through four layers of cheesecloth [5,6,11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these sources is ruminant feces; however, results have been inconsistent. For example, fecal inoculum has been demonstrated to be effective for in vitro gas production studies (54) ; nonetheless, fecal inoculum from sheep was not comparable to fresh ruminal fluid when evaluating in vitro dry matter digestibility (55) . In addition, other studies, have revealed that fecal inoculum does not perform as good as ruminal fluid in in vitro fermentation techniques (55,56) , which may be due to differences in the bacterial populations between the rumen and the lower gastrointestinal tract (57) .…”
Section: Effect Of Fermentation Substrate On Fermentation Kinetics Anmentioning
confidence: 99%